Radiofrequency ablation of liver VX2 tumor: experimental results with MR diffusion-weighted imaging at 3.0T. - Yubao Liu (Public Library of Science (PLoS), 2014)
Purpose To evaluate the value of DWI in detecting the lesions of pre- and post-radiofrequency ablation (RFA) of the rabbit liver VX2 tumors. Materials and methods Twenty-two New Zealand White rabbits were tested. The protocol was approved by the Committee on the Ethics of Animal Experiments. Twenty separate tumor fragments were implanted into the livers of 20 rabbits, the liver was exposed by performing midline laparotomy. 3.0T MR DWI (b = 0, 200, 400, 600, 800,1000 s/mm2) were performed 14-21 days after tumor implantation (mean, 17 days) in the 18 tumor-bearing animals. Then RFA was performed in the 18 tumor-bearing animals and in the two healthy animals. 3.0T MR DWI was performed 7-10 days after RFA (mean, 8 days). Pathology exam was performed immediately after the completion of post- RFA MR imaging. Analyzing the features of MRI and ADC values in the pre- and post- RFA lesions of the VX2 tumors, and histopathologic results were compared with imaging findings. Results The difference of ADC value between viable tumor and normal liver parenchyma was significant (P<.001). After RFA, when b = 200, 400, 600, 800, 1000 s/mm2, the differences of ADC values of viable tumor, granulation tissue, necrosis, normal liver parenchyma were significant (P<.001). At the time the animals were sacrificed after RFA and MR imaging, histopathologic results of local viable tumors were found in 9 (50%) of the 18 treated tumors. Macroscopic viable tumors were found at the RFA sites in 3 (17%), all 3 macroscopic viable tumors were visualized at the periphery of the RFA areas. Conclusions 3.0T MR DWI can be used to follow up the progress of the RFA lesion, it is useful in detecting different tissues after RFA, and it is valuable in the further clinical research.